2018
DOI: 10.1021/acs.macromol.8b00344
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Viscoelasticity of Hydrogen-Bonded Polymeric Materials through Solvent Composition

Abstract: The interactions between polymer molecules in solution are strongly affected by the way that the constituent polymers interact with the solvent. In this work, we use a mixed solvent system (dimethyl sulfoxide and ethylene glycol) to tailor the strength of the hydrogen-bonding interactions between partially quaternized poly­(4-vinylpyridine) [QVP] and poly­(methacrylic acid) [PMAA]. The charge introduced by the quaternization reaction enables homogeneous solutions to be formed over a large concentration range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…As f d increased from 10 to 100 vol %, the swelling ratio in length of the gel, S , increased from 1 to 2.5 (Figure b). Different S of gel in the mixture solution was due to the different solvent quality for the solubility of polymer chains and different dissociation degree of the hydrogen bonds . Then, the swollen gel was transferred into a large amount of water, in which the gel contacted its volume to some extent and reached the equilibrium state.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As f d increased from 10 to 100 vol %, the swelling ratio in length of the gel, S , increased from 1 to 2.5 (Figure b). Different S of gel in the mixture solution was due to the different solvent quality for the solubility of polymer chains and different dissociation degree of the hydrogen bonds . Then, the swollen gel was transferred into a large amount of water, in which the gel contacted its volume to some extent and reached the equilibrium state.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Different S of gel in the mixture solution was due to the different solvent quality for the solubility of polymer chains and different dissociation degree of the hydrogen bonds. 54 Then, the swollen gel was transferred into a large amount of water, in which the gel contacted its volume to some extent and reached the equilibrium state. The volume contraction of gel was related to the re-formation of hydrogen bonds.…”
Section: Tunable Properties Of the Hydrogelmentioning
confidence: 99%
“…Quite similarly, it has been recently reported that the solvent composition tunes in a controlled fashion the strength of the hydrogen bond-based cross-links between two polyelectrolytes, leading to frequency shifts of the frequency-dependent complex moduli of polymer complexes. 17 In these examples, the solvent composition influences uniquely the strength and/or amount of crosslinks between polymer chains, presumably not the chain conformation itself. In this framework, studies on the cosolvency or co-nonsolvency effect on polymer gels are rather scarce.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In ref the chemical cross-linking of gelatin is induced by an external additive, whose solubility depends on the water/ethanol content, thus leading to gels whose viscoelasticity depends on the solvent composition. Quite similarly, it has been recently reported that the solvent composition tunes in a controlled fashion the strength of the hydrogen bond-based cross-links between two polyelectrolytes, leading to frequency shifts of the frequency-dependent complex moduli of polymer complexes . In these examples, the solvent composition influences uniquely the strength and/or amount of cross-links between polymer chains, presumably not the chain conformation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Quite similarly, it has been recently reported that the solvent composition tunes in a controlled fashion the strength of the hydrogen bonds-based crosslinks between two polyelectrolytes, leading to frequency shifts of the frequency dependent complex moduli of polymer complexes. 17 In these examples, the solvent composition influences uniquely the strength and/or amount of crosslinks between polymer chains, presumably not the chain conformation itself. In this framework, studies on co-solvency or co-nonsolvency effect on polymer gels are rather scarce.…”
Section: Introductionmentioning
confidence: 99%